PENGARUH BUKU BACAAN INTERAKTIF BERBASIS AUGMENTED REALITY (AR) TERHADAP PENINGKATAN KEMAMPUAN PENGUASAAN KOSAKATA SISWA KELAS II SDN 066056 MEDAN DENAI - Rahmadani; Edizal Hatmi; Wildansyah Lubis; Halimatussakdiah; Masta Marselina Sembiring (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of using Augmented Reality (AR)-based interactive reading books on improving vocabulary mastery of second-grade students at UPT SD Negeri 066056 Medan Denai in the 2025/2026 Academic Year. This study used a quasi-experimental design with a non-equivalent control group design. The population in this study were all second-grade students, consisting of two classes: class II-A as the experimental class and class II-B as the control class. The study sample consisted of 40 students, with each class consisting of 20 students. The research instrument used was a vocabulary mastery test in the form of a pre-test and a post-test consisting of 20 multiple-choice questions. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using the Independent Sample t-test. The results of the data analysis showed that the average post-test score in the experimental class was 75.5, higher than the control class, which was 65.5. Based on the t-test results, the α-value of 2.529 and α-value of 2.024 were obtained at a significance level (Sig.) of 0.05. Therefore, H0 was rejected and Ha was accepted. Thus, it can be concluded that the use of interactive reading books based on Augmented Reality (AR) significantly improved vocabulary mastery among second-grade students at UPT SD Negeri 066056 Medan Denai